Gender, policy, politics, and work: feminist comparative and transnational research - Gottfried, Heidi; Reese, Laura (2003)
This article reviews feminist comparative and transnational research on workplace policy, politics and the state. The first section examines a range of theoretical approaches to the topic. We then present a variety of methodologies for conducting comparative and transnational research on policy developments. Informed by a number of case studies included in the symposium, we explore the dynamics and determinants, both national and supranational, of policy formation and its impacts. Finally, we tease out the implicit and explicit notions of gender equity for future policy analysis. - Reproduced.
Keywords: Women